Urinary hydroxyproline excretion in coalworkers' pneumoconiosis - Resnick, H. (1969)
Resnick, H., Lapp, N. L., and Morgan, W. K. C. (1969).Brit. J. industr. Med.,26, 135-138. Urinary hydroxyproline excretion in coalworkers' pneumoconiosis. As there is an increased formation of one or all the fibrous proteins in coalworkers' pneumoconiosis, it was felt that a study of the turnover rate of these proteins might shed some light on the pathogenesis of the disease. Urinary hydroxyproline excretion was therefore studied in a group of miners, of whom 19 had simple pneumoconiosis and five had progressive massive fibrosis. No significant deviation from the normal was found.